Market participation of smallholder groundnut farmers in Northern Ghana: Generalised double-hurdle model approach - Dominic Tasila Konja; Franklin Nantui Mabe (Cogent Economics & Finance, 2023)
Market participation is both a cause and a consequence of economic development. Markets offer households the opportunity to specialize according to comparative advantage and thereby enjoy welfare gains from trade. The current literature on product marketing in Ghana is inadequate for designing and implementing effective policies to overcome problems in the marketing system, especially leguminous crops. Based on this, the study analyses the determinants of groundnut farmers' decision to participate and the level of market participation in Northern Ghana using cross-sectional data from 250 smallholder farmers. We employed the generalized double hurdle model to analyse the objectives of this study. On average, the study found that 62% of groundnut output harvested by farm households in Northern Ghana was sold on the market. The most significant determinants of market participation decision and intensity of participation in the groundnut market include extension service, distance to output market, farmer-based organization, off-farm income, output price, use of improved groundnut variety, and access to transport. We recommend that strategies and policies aiming at promoting smallholder commercialization should focus on providing rural infrastructure, market-oriented extension services, and forming farmer groups for collective marketing.
Keywords: 330; generalised linear model; Market participation; Northern Ghana; probit model; smallholder farmers